Contribution of Adversity Quotient, Self Awareness and Demographic Factors to Student Career Maturity - Wahyu Kurniawan; Daharnis Daharnis; Yeni Karneli (International Journal of Research in Counseling and Education, 2020)
One of the purposes of vocational school (SMK) is as an education facility to prepare alumni who are ready to enter work field, but in contrary the highest number of unemployed in West Sumatra is dominated by SMK alumni. This research aims to describe the contribution of adversity quotient, self awareness and demographic factors to student career maturity. The study was conducted using quantitative descriptive methods. The research population were students of class XII at SMKN6 Padang as many as 392 students and a sample of research were 198 students. The technique used in this research waspurposive sampling technique. The instrument used was a adversity quotient, self awareness and career maturity scale was using Likert model, and the research data was analyzed using simple regression and multiple regression with dummy variables. The research findings prove that: (1) adversity quotient has an effective contribution of 23% to student career maturity, (2) self awareness contributing as much as 37.9% to career maturity, (3) gender does not contribute to career maturity,(4) socioeconomic status contributes 4.9% to student career maturity, and (6) there were 47.8% of contributions together with adversity quotient, self awareness, gender and socioeconomic status on students' career maturity. This result show that student’s career maturity was not influenced by one variable only but adversity quotient, self awareness and demographic factor all together contribute in forming student’s career maturity. Therefore, increase in career maturity as an attempt to prepare students prior to entering work field could be done by optimizing adversity quotient level and self awareness while also considering demographic factor of each students.